MOTIVATION TO LEARN INDONESIAN AMONG STUDENTS OF SMA NEGERI 1 BANGSRI JEPARA REGENCY - Fauziah, Salsa Anabela; Ulumuddin, Arisul; Sidiq Budiawan, Raden Yusuf (LEMBAGA PENELITIAN DAN PENGABDIAN PADA MASYARAKAT, 2025)
Many students show a lack of enthusiasm in participating in Indonesian language lessons. Based on their passive attitude during the learning process, where students tend to be more silent and less actively participate. The purpose of this research is to describe the causes and effects of learning motivation on the students of SMA Negeri 1 Bangsri, Jepara Regency. This study uses qualitative methods. Students' learning motivation in the Indonesian Language subject at SMA Negeri 1 Bangsri shows a quite significant variation. The data sources for this research are the teachers and students of SMA Negeri 1 Bangsri, while the data in this study is the students' learning motivation in the Indonesian language subject using interviews with teachers and students. Qualitative data analysis is a method used to organize, analyze, and interpret non-numeric data, especially in exploratory research. The results of the interview research conducted with Indonesian language teachers and students show a low level of learning motivation due to several influencing factors. Several factors that influence the motivation to learn Indonesian at SMA Negeri 1 Bangsri include internal and external factors. By implementing innovative learning strategies and creating a supportive learning environment, it is hoped that students' motivation to learn Indonesian can significantly increase.